The Impact of Corruption on Economic Growth of Nigeria: A New Evidence - Olabisi, Olabode Eric (FEB Universitas Sultan Ageng Tirtayasa, 2024)
In most African countries, including Nigeria, lack of quality public sector service, disobedience to the rule of law, and poor institutional frameworks are prevalent, and these create an avenue for corruption. Hence, this study investigates the impact of corruption on Nigerian economic growth from 1999 to 2021.While previous researchers concentrated on the causes of corruption and its transmission channels to the economy, the current study focuses on its impacts. Applying the autoregressive distributed lags model, findings show that a 1% increase in corruption decreases the economic growth rate by 0.29%. Amongothergrowthdeterminants other growth determinants tested in this study, population reveals a positive impact on the economic growth of Nigeria. Thus, the empirical outcome shows that a 1% increase in population increases the country's economic growth by 3%. This is true because population has the tendency to drive aggregate demand and, thus, increase growth. The policy recommendations of the paper are contained in the body of the work.